Real‐life 3D therapy failure: Analysis of NS5A 93H RAS plus 108 K polymorphism in complex with ombitasvir by molecular modeling. Issue 7 (31st March 2018) - Marascio, Nadia; Pavia, Grazia; Romeo, Isabella; Talarico, Carmine; Di Salvo, Sebastiano; Reale, Mariaconcetta; Marano, Vito; Barreca, Giorgio Settimo; Fabiani, Fernanda; Perrotti, Nicola; De Siena, Massimo; Giancotti, Francesca; et al.
Abstract : We report a real‐life 3D therapy failure in a patient treated with ombitasvir (OMV)/paritaprevir/ritonavir and dasabuvir without ribavirin (3D‐R). He had therapy failure at week 12 after the end of treatment. We detected resistance‐associated substitutions (RASs) plus polymorphisms on NS3, NS5A, and NS5B target regions by population sequencing (15% cut‐off) at baseline, at relapse and during follow‐up. About this, NS5A RASs generally persist longer than resistances in the other target genes and may impact treatment outcome. Therefore, to evaluate OMV drug‐resistance mechanism, we studied the acquired RAS plus polymorphisms on NS5A phosphoprotein by computational studies. OMV showed a higher affinity towards baseline and 93H/108 K mutant structure (follow‐up) with respect to 93H/R108 mutant structure (relapse) on phosphoprotein. By Molecular Dynamics simulations (MDs), structural information about the protein stability in presence of OMV were observed. According to our data, molecular modeling approach has proved to be a powerful method to evaluate the impact of these RASs plus specific amino acid (AA) changes on phosphoprotein.